Macrocyclic tetra-phosporus compounds and protection of bridge - Vidal, M. (1998)
The synthesis ot macrocyclic tetraphosporus compounds, constitute the primary objetive of this works. The reactivity of these compounds and study ot their complexing ability are also described. In this review is presented an overview of the state of the researsh in this area.